A brave new world? LNG contracts in the context of market turbulence and an uncertain future - Jack Sharples (The Oxford Institute for Energy Studies, 2023)
In 2022, the global LNG market faced exceptional levels of turbulence, as European gas buyers sought to offset the loss of Russian pipeline supply with an unprecedented increase in LNG imports. The ability of European buyers to access those LNG supplies was facilitated by the flexibility embedded in the global LNG market, including the ability to purchase spot cargoes from aggregators and traders. This paper argues that the LNG demand seen in Europe in 2022-23 is not temporary, but is now structural, and set to remain for the rest of the decade and likely beyond. In this context, European LNG buyers must reconcile the need to secure gas supply in the short-term with the long-term imperatives of decarbonisation, while LNG export project developers will only continue adding supply to the global market on the basis of firm offtake commitments, under binding long-term contracts. The key question is: how to reconcile the short and long-term needs of buyers and project developers, to ensure that the market remains sufficiently well supplied to manage an orderly energy transition? In addressing this question, the standout conclusions of this paper are: While the global LNG market is set to remain tight until 2025, the second half of the decade will see a substantial wave of new supply based on projects that have already taken FID. However, the supply-side outlook beyond 2030 is highly uncertain. If global LNG demand continues to grow, the market will need additional supply from projects that need to take FID in the mid-2020s, in order to launch around 2030, or else face the shift from over-supply to under-supply akin to that seen in Europe between 2019/20 and 2021/22. This uncertainty raises the possibility of several possible scenarios. In a 'structural imbalance' scenario, the market could be under-supplied if insufficient supply-side FIDs are taken in the mid-2020s, or over-supplied if supply continues grow faster than demand beyond 2030. A more benign, 'structural balance' scenario could see new liquefaction capacity taking FID in the mid-2020s on the basis of offtake agreements mostly with aggregators (portfolio players), who assume volume risk in return for earning a premium on re-selling to Europe and Asia, and end users who will only be willing to commit to contracts with destination and re-sale flexibility. Aggregators will play a vital role in reconciling the short and long-term needs of LNG producers and consumers. Their willingness to sign new, binding offtake agreements over the next several years, their confidence in their ability to re-sell those volumes, and the ability of LNG project developers to leverage those offtake agreements and raise finance sufficient to take FID, will be indicative of both the state of the LNG industry in the mid-2020s, and how it views its own future post-2030.
Keywords: 330; Europe; Gas; LNG; LNG contracts; Qatar; United States